(untitled) (REMUNOM, 2025)
sugar-energy sector plays a fundamental role in the Brazilian economy and society, with a strong participation in the national GDP and growing social and environmental relevance. This study analyzed the economic and financial health of a Brazilian company in the sector between 2015 and 2020, using liquidity, capital structure, and profitability indicators. The data were obtained through documentary analysis, based on balance sheets and quarterly financial statements available on the company’s investor relations website. The results showed current and dry liquidity ratios higher than the market averages, indicating good solvency capacity. As for the capital structure, there was an increase in the use of third-party capital to finance the company’s activities. In terms of profitability, the net margin, ROI and ROE indicators were positive throughout the period analyzed, suggesting consistent profitability and good financial health.